Contemporary CSR model: Conceptualization, scale development, and validation to measure consumer perceptions - Karpal Singh Dara Singh; Munir A. Abbasi; Ghazanfar Ali Abbasi; Azlan Amran; Essia Ries Ahmed (International Journal of Business Science & Applied Management (IJBSAM), 2021)
The objectives of this article are twofold. The first objective is to review three CSR models to propose a new contemporary model of CSR, representing the significant commitments and practices organisations should undertake in their quest to become socially responsible. The second objective is to develop and validate a new CSR scale to measure consumer perceptions of organizations' CSR performance-based Drawing on Carroll's CSR, Vissers' CSR 2.0 models, and the Bursa Malaysia CSR framework, the research proposes a conceptual framework. A CSR scale was developed and validated through a large-scale empirical study measuring consumer perceptions involving 909 respondents from Malaysia. The CSR scale items were tested and validated via exploratory factor analysis and reliability analysis. As a result, the new CSR model consisted of six main dimensions representing key CSR commitments, and a 27 item CSR scale was validated. The conceptual framework adds value by providing managers and policymakers with a new way of looking at CSR holistically and comprehensively, enabling the development of effective CSR initiatives and strategies. In addition, the contemporary scale provides a reliable and valid instrument to measure consumers' perceptions of their CSR initiatives.
Keywords: 650; Contemporary CSR model; scale development; consumer perceptions